Determination Of Dolog’s Ideal Warehouse Based On Minimum Logistics Cost - Eriana Astuty (Jurnal Teknik Industri, 2014)
Most of indonesian societies consume rice as staple food and therefore need the amount of rice that meet the demand within the infinite time. Food warehouse is needed in order to maintain supplies. Rice warehouse should be located in the strategic location so that it is easy to reach and to avoid the stagnation of supply. In addition, that can also be useful for financing streamline because it can minimize the logistics costs. Dolog as a unit of the agency Bulog is responsible to maintain the stability and availability of basic foodstuffs in the region of Indonesia and to participate in the procurement and supply of basic foodstuffs especially rice. To carry out its duties, Dolog also must have an ideal rice warehouse which its capacity should meet the demand of the rice according to the market supplied. The result of cluster method used in this research suggests that there are three ideal warehouse locations to supply main markets in Bandung. If the three ideal warehouse locations are compared with the existing warehouse, proposed warehouse location donates saving about IDR 45,032,203 per year or approximately IDR 125,000 per day. So there are two solutions can be taken by Dolog that the first is open new warehouses and the second is using the old warehouse and adding the shortage storage capacity by opening additional warehouse at ± 6,000 tons.